A virtuous woman : a novel - Gibbons, Kaye. (Chapel Hill, NC: Algonquin Books, 1997)
A young widower looks back on his memories of his wife and their life together.
Keywords: Widows -- Fiction; Tenant farmers -- Fiction; Women authors, American -- Southern States; Women authors, American -- North Carolina; Love stories